Enhancing wheat yield potential through the QTL QFFE.perg-5A and QFEm.perg-3A associated to spike fruiting efficiency : insights from plot-level analysis - Pretini, Nicole (2025)
Wheat (Triticum aestivum L.) is a key global crop, essential for food security. To enhance its productivity this study focused on two quantitative trait loci (QTL), QFFE.perg-5A and QFEm.perg-3A, previously associated with fruiting efficiency at the spike level. We extended the analysis to the plot level to evaluate their impact on yield, thousand grain weight, and related traits, using a double haploid population of 102 lines in three environments. The results showed an epistatic interaction between a QTL for spike dry weight and grain number per spike. QFFE.perg-5A showed no interaction with the environment, increasing fruiting efficiency (13-15%), grain number per spike (7%), and spike number per unit area (9%), leading to an 8% rise in grain number per unit area and a 5% yield increase. In contrast, QFEm.perg-3A's impact depended on the environment. This study connects spike-level QTL analysis with plot-level effects, providing valuable insights for breeding programs to improve wheat varieties with desirable traits and increased productivity.